Seafood from Catch and Aquaculture for a Sustainable Supply - Poli, Bianca Maria; Parisi, Giuliana (Proceedings e report, 2008)
For the fist time, the WEFTA Annual Meeting takes place in Italy, at Firenze on September 17th to 19th, 2008. The WEFTA 2008 theme is "Seafood from Catch and Aquaculture for a Sustainable Supply". WEFTA 2008 aims the gathering of international researchers, scientists and technicians, as well as professionals from seafood Industry, particularly involved in research and development, quality control and management for a three-day conference involving scientific and technical presentations, discussion and social contacts. The book of abstracts contains the 117 full and short abstracts of the communications presented in this 38th WEFTA Annual Meeting by scientists coming from several European Countries but also from USA, Canada, Brazil and Japan, able to give up-to-date information of great interest, useful for the development of scientific knowledge in much of the seafood issues.